The Destabilization of Symbolic Boundaries in the Consumption of Translated Fiction - Tekgül, Duygu (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2017)
For several decades, the positive norms of cosmopolitanism and omnivorousness have dominated cultural consumption in Britain. This paper will discuss the implications of these interrelated affinities in the popular reception of fiction in translation. Ethnographic data for the study has been collected mostly through participant observation with book club members in the UK. Through an analysis of statements made by readers, the article will illustrate how reading and discussing fiction in translation encourages readers to mobilize their international cultural capital and how horizontal and vertical boundaries between genres become blurred. Consequently, individual translations may become “upgraded” or “downgraded” in aesthetic terms, especially in the ways these books have been packaged and marketed to readers.